Tarian Padhoge dalam Ritual Adat Ngkadhe di Desa Biwinapada - Mahmudin Mahmudin; Ahmat Keke (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This study aims to determine the symbolic meaning and function of the Padhoge dance in the traditional Ngkadhe ritual in the village of Biwinapada. The theory used refers to the functional theory proposed by Radcliffe-Brown, which describes the functional unity of a social system as a certain assumption, where antagonism between groups in society is an important feature of every social system. The author uses a qualitative descriptive method by carrying out several stages, namely, observation, regular interviews, in-depth interviews and involved observations, the data obtained from which is then analyzed using the ethnographic method. As for the results of the study, it can be concluded that the traditional procession of the ngkadhe ceremony begins with planning by the families who will isolate their daughters. The traditional ceremony was opened by a parable (traditional chief). During this time, those who lead the girls in the ka'ombo are called bhisa. The girls will be in ombo for 4 days 4 nights. The music player that accompanies the isolation ceremony is called pande rambi. Pande rambi only came to play music at the opening ceremony on the morning of the third day and on the fourth day when the traditional ngkadhe ceremony ended. In ka'ombo, the girls will use cold powder and must follow the rules during the procession of the traditional ceremony. On the third day, the kaombo girls will use the patirangga and learn to dance the Padhoge dance.